Analysis of Antiapoptosis Effect of Netrin-1 on Ischemic Stroke and Its Molecular Mechanism under Deleted in Colon Cancer/Extracellular Signal-Regulated Kinase Signaling Pathway. - Wang, Kai; Rong, Liangqun; Wei, Xiu'e; Zhang, Qingxiu (BioMed Research International, 2020)
To analyze the regulatory effect of Netrin-1 in ischemic stroke and its influence on Deleted in Colon Cancer (DCC)/Extracellular Signal-regulated Kinase (ERK) signaling pathway, 20 male rats were selected to construct the rat model of middle cerebral artery occlusion (MCAO), 10 normal rats were selected as healthy controls (Normal Saline (NS)), and they were divided into the MCAO+Netrin-1 group, MCAO group, and NS group according to different treatment schemes. The positive expression of Netrin-1 was detected by immunostaining, magnetic resonance imaging (MRI) was adopted to detect the percentage of rat cerebral infarct volume in the cerebral hemispheres, and Modified Neurological Severity Score (mNSS) was adopted to evaluate postoperative neurological function in rats. Besides, a tunnel staining experiment was applied to detect the apoptosis rate of rat neurons, the sticker removal test was applied to evaluate the postoperative sensory function of rats, and fluorescence staining was adopted to detect the expression of DCC and ERK in rats. The results showed that the percentage of cerebral infarction volume in the cerebral hemispheres of the MCAO+Netrin-1 group was higher than that of the MCAO and NS groups (P < 0.05); in the MCAO+Netrin-1 group, the MCAO mNSS scoring and the time spent in the sticker removal test were lower than the MCAO group (P < 0.05); the apoptosis rate of rats in the MCAO+Netrin-1 group was lower than that in the MCAO group (P < 0.05); the average fluorescence intensity of DCC and p-ERK in the MCAO+Netrin-1 group was higher than that in the MCAO group (P < 0.05); the average fluorescence intensity of p-ERK in the MCAO+Netrin-1 group was higher than that in the MCAO group (P < 0.05). In short, Netrin-1 can effectively reduce the brain tissue damage in rats with ischemic stroke, improve the nerve function and sensory function of rats, and inhibit neuronal cell apoptosis. Netrin-1 can promote DCC expression and ERK phosphorylation, and the EPK signaling pathway may be involved in the antiapoptotic effect of Netrin-1.